Rosiglitazone Increases Cerebral Klotho Expression to Reverse Baroreflex in Type 1-Like Diabetic Rats. (13th February 2014) - Chen, Li-Jen; Cheng, Meng-Fu; Ku, Po-Ming; Lin, Jia-Wei
Abstract : Reduced baroreflex sensitivity (BRS) is widely observed in diabetic human and animals. Rosiglitazone is one of the clinically used thiazolidinediones (TZD) known as PPAR γ agonist. Additionally, the klotho protein produced from choroid plexus in the central nervous system is regulated by PPAR γ . In an attempt to develop the new therapeutic strategy, we treated streptozotocin-induced diabetic rats (STZ) with rosiglitazone (STZ + TZD) orally at 10 mg/kg for 7 days. Also, STZ rats were subjected to intracerebroventricular (ICV) infusion of recombinant klotho at a dose of 3 μ g/2.5 μ L via syringe pump (8 μ g/hr) daily for 7 days. The BRS and heart rate variability were then estimated under challenge with a depressor dose of sodium nitroprusside (50 μ g/kg) or a pressor dose of phenylephrine (8 μ g/kg) through an intravenous injection. Lower expression of klotho in medulla oblongata of diabetic rats was identified. Cerebral infusion of recombinant klotho or oral administration of rosiglitazone reversed BRS in diabetic rats. In conclusion, recovery of the decreased klotho in brain induced by rosiglitazone may restore the impaired BRS in diabetic rats. Thus, rosiglitazone is useful to reverse the reduced BRS through increasing cerebral klotho in diabetic disorders.